De doctorants à directeurs de recherche : accompagnement reçu et dispensé - Claire Duchesne; Lucie Le Callonnec; Nathalie Gagnon (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The supervision of doctoral research requires from university professors a strong commitment to the student and the use of high theoretical and methodological knowledge, as well as supervisory and support skills. When the supervisor has little experience in carrying out research and teaching functions, such as new university professors, the challenge is big and the consequences can be significant. This article examines the type of support 16 new faculty members at Canadian universities received when they were students and how they currently supervise their students.